Electropolymerised molecularly-imprinted polymer for the detection of serum Vitamin D using Box-Behnken design - Mohd Azerulazree Jamilan; Zainiharyati Mohd Zain; Kavirajaa Pandian Sambasevam; Faizatul Shimal Mehamod; Balqis Kamarudin; Mohd Fairulnizal Md Noh (Discover Applied Sciences)
Abstract An in-situ optimised electro-polymerised molecularly-imprinted polymer (MIP) on single-walled carbon nanotube-modified screen-printed carbon electrode (SWCNT/SPCE) embedded on a molecularly-imprinted poly(styrene-co–N-(3-aminopropyl)methacrylamide) (denoted as eMIP/SWCNT/SPCE) using the Box-Behnken Design (BBD) was able to reduce chemical consumption and process time. The in-situ optimisation steps resulted in a 1:25 template-monomer ratio, 19 cyclic voltammetry (CV) cycle number, and 250 mV/s of scan rate for 50 µg/L of 25-hydroxyvitamin D3 (25-OHD3), which was incubated for 10 min, prior wet laboratory work. The selectivity was controlled by comparing the response from MIP to non-imprinted polymer (NIP), producing an imprinting factor (IF) value of 3.1 at optimised condition. The calibration was plotted from 10.0 to 30.0 µg/L of 25-OHD3 with an limit of detection (LOD) of 1.8 µg/L and limit of quantification (LOQ) of 5.5 µg/L. The obtained 25-OHD3 concentration in the serum samples of SRM978f was 12.9 ± 3.3 µg/L (reference value 14.0 ± 4.6 µg/L) and 10 µg/L of spiked serum SRM909c was 10.3 ± 3.6 µg/L. The modified sensor eMIP/SWCNT/SPCE was able to recover the real sample result from 92.1% to 103.0%.